2015
DOI: 10.1007/s00259-015-3154-y
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrosis after lumbar spinal fusion: the role of 18F-fluoride PET/CT

Abstract: PurposePainful pseudarthrosis is one of the most important indications for (revision) surgery after spinal fusion procedures. If pseudarthrosis is the source of recurrent pain it may require revision surgery. It is therefore of great clinical importance to ascertain if it is the source of such pain. The correlation between findings on conventional imaging (plain radiography and CT) and clinical well-being has been shown to be moderate. The goal of this study was to determine the possible role of 18F-fluoride P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…Also, there are various parameters defined on CT scan including extra-graft bridging bone and intra-graft bridging bone, but the results are inconsistent with other radiographic indicators and not reliable in all cases [9]. In the study published by Peters et al [10], they found a better technique for the diagnosis of pseudoarthrosis. They concluded that the 18 F-fluoride positron emission tomography (PET) scan has better accuracy compared to the CT scan in symptomatic patients, but in asymptomatic patients, CT scan is better.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are various parameters defined on CT scan including extra-graft bridging bone and intra-graft bridging bone, but the results are inconsistent with other radiographic indicators and not reliable in all cases [9]. In the study published by Peters et al [10], they found a better technique for the diagnosis of pseudoarthrosis. They concluded that the 18 F-fluoride positron emission tomography (PET) scan has better accuracy compared to the CT scan in symptomatic patients, but in asymptomatic patients, CT scan is better.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we believe that the degree of structural damage caused by PVO is greater than that observed in a benign fracture, which may account for the higher 18 F-FDG uptake in PVO. Increased 18 F-FDG uptake on the intervertebral structure is also correlated with the occurrence and magnitude of endplate subsidence [20]. Suto et al [21] reported that a higher 18 F-FDG uptake and ESR are related to the disease activity and severity of joint destruction in rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…121 Spinal orthopedics is another area that may benefit from NaF-PET, which may have a role in predicting healing and identifying complications such as nonunion, pseudarthrosis, infection, and hardware loosening. [126][127][128][129][130][131] In pediatrics, Grant 27 reported utility in determining the cause of pain in children who underwent spinal fusion surgery for scoliosis. Fischer and colleagues 132 studied 20 patients who underwent cervical or lumbar intercorporal fusion and found that increased NaF activity could be visualized in cervical cages for up to 8 years after intervention and up to 10 years in lumbar cages (Fig.…”
Section: Orthopedic Complicationsmentioning
confidence: 99%